On the Role of Hydrolyzable Metal Cations in the Adsorption of Anionic Surfactants on Negatively Charged Surfaces - Weber, Christian; Peuker, Urs A. (Frontiers in Materials, 2020)
The role of hydrolyzable metal ions in the adsorption of anionic surfactants on a negatively charge surface is studied by electrophoresis and phase transfer experiments. The notion that the presence of such hydrolyzable species (activators) can promote flotation is not new, but a detailed mechanistic explanation is lacking. We relate the role of activators to the phenomenon of overcharging, which has been studied rather extensively within colloid and interface science. The experiments conducted in this article show that overcharging is a necessary condition for the adsorption of an anionic surfactant on a negatively charged surface and that the hydrophobization of the studied particles is most effective when overcharging is most pronounced.